PENGARUH KEBIJAKAN DIVIDEN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN GCG SEBAGAI MODERASI - Ashary, Feby (Fakultas Ekonomi Universitas Tadulako, 2019)
This study aims to determine the effect of dividend and leverage policy on firm value in manufacturing sector in the Indonesia Stock Exchange (IDX) with good corporate governance as moderating variable for the 2013-2017 period. The population in this study amounted to 130 companies. The research sample of 17 companies using purposive sampling techniques. The analytical tool used is panel data regression with moderate regression analysis (MRA). The results showed that dividend policy (DPR) and leverage (DER) simultaneously had positive and significant effect on firm value (Q). Partial testing shows that dividend policy and leverage have positive and significant effect on firm value. Whereas GCG (KM) as moderating weakens the relationship between dividend policy on firm value and leverage on firm value.